Wort Stripping Thermodynamic Considerations on the Evaporation of Aroma Substances in Continuous Desorption Processes - Feilner, Roland; Rehmann, Dirk; Methner, Frank-Jürgen; Baldus, Matthias; Kunz, thomas; Scheuren, Hans (BrewingScience, 2013)
In modern brewing technology, the task of the evaporation process during wort boiling is not so much to adjust the original extract as rather, besides hop isomerisation and protein precipitation, to take care of eliminating undesirable aroma substances to a level below their sensorial threshold. To achieve this in practice, in addition to the widespread use of atmospheric boiling, combinations of heat retention and evaporation are frequently implemented as well as boiling in high pressure or low pressure ranges in connection with re-evaporation systems. These additionally employed evaporators are frequently integrated in the form of a vacuum apparatus or a stripping process following the removal of the hot trub. Stripping is usually to be found as a continuous process whereby a gas flow is responsible for effecting the evaporation of the liquid and hence the desorption of a corresponding portion of the aroma components contained therein.The new development of the stripping system presented here is not based on a conventional evaporation process as, for example, is the case with expansion evaporation and the use of supplementary energy associated therewith, but rather on the basis of evaporation utilising the latent heat of the wort. With respect to the technological procedure, this process step is comparable to the evaporation process formerly employed with a coolship. Due to the large phase boundary at the wort surface and the very extensive gaseous space lying above that surface ? combined with a continual air exchange above the wort surface ? continuous evaporation resulting from the wort which is cooling down is possible. When implemented with consistent technological procedures and apparatus, this efficient evaporation process, in connection with an optimised boiling program, leads to significantly improved energy efficiency in the preparation of the wort. As the following statements substantiate, the utilisation of such a system is also conducive to the reduction of undesirable aroma substances and thus to the enhancement of the composition of the wort. The shortening of the boiling time and, along with, it a slighter thermal load and a minimisation of the total evaporation contribute to energy savings.